2017
DOI: 10.1098/rsfs.2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and utility of amyloid fibrils formed by short amyloidogenic peptides

Abstract: Amyloidogenic peptides are well known for their involvement in diseases such as type 2 diabetes and Alzheimer's disease. However, more recently, amyloid fibrils have been shown to provide scaffolding and protection as functional materials in a range of organisms from bacteria to humans. These roles highlight the incredible tensile strength of the cross-β amyloid architecture. Many amino acid sequences are able to self-assemble to form amyloid with a cross-β core. Here we describe our recent advances in underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…Protein misfolding induces aberrant aggregation, and often results in the formation of amyloid fibrils that are associated with more than 40 amyloidoses and neurodegenerative diseases, including Alzheimer's and Parkinson's diseases (1)(2)(3)(4). Although needle-like morphology and cross-β structure are common basic properties of amyloid fibrils, it has been revealed that amyloid fibrils show microscopic structural diversity (4)(5)(6). Differences in amyloid structure are observed even when amino acid sequence is identical or very similar, and details of these different structures have recently been clarified at an atomic level owing to the progress of cryoelectron microscopy (cryo-EM) (7,8) and solid-state NMR spectroscopy (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Protein misfolding induces aberrant aggregation, and often results in the formation of amyloid fibrils that are associated with more than 40 amyloidoses and neurodegenerative diseases, including Alzheimer's and Parkinson's diseases (1)(2)(3)(4). Although needle-like morphology and cross-β structure are common basic properties of amyloid fibrils, it has been revealed that amyloid fibrils show microscopic structural diversity (4)(5)(6). Differences in amyloid structure are observed even when amino acid sequence is identical or very similar, and details of these different structures have recently been clarified at an atomic level owing to the progress of cryoelectron microscopy (cryo-EM) (7,8) and solid-state NMR spectroscopy (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…While amyloids are notoriously stable against modest changes in conditions, they can be disassembled to their constituent molecules through sonication [9]. This confirms the absence of permanent chemical bonding; despite their structural complexities, amyloid aggregates are stabilised by a balance of contributions from hydrogen bonding, the hydrophobic effect, aromatic and electrostatic interactions [10]. After sonication, re-aggregation (i.e.…”
Section: Introductionmentioning
confidence: 69%
“…The central section is noteworthy (referred to as [26][27][28][29][30][31][32][33][34][35], which has a very low RD value in all forms. Figure 9A,B) shows very high similarity over the entire length of the chain with significantly different intrinsic hydrophobicity characteristics ( Figure 9A).…”
Section: Analysis Of T and O Profiles (mentioning
confidence: 99%
“…In the current and other works of our team, an external factor is studied, which is the impact of the aquatic environment. Its active participation in the folding process directs this process towards the generation of a hydrophobic nucleus, which is a phenomenon commonly observed for bipolar molecules in the case of spontaneous formation of the spherical micelle [31][32][33][34][35]. Protein can be treated as a specific spherical micelle, which due to diversity (20 different forms of bipolarity) and limitation of the number of degrees of freedom (amino acids connected by covalent bonds) is able to create a form of micelles with an ideal distribution of hydrophobicity (with hydrophobic amino acids in the center, and polar on surface) only in exceptional cases.…”
Section: Introductionmentioning
confidence: 97%